A Restructured Hospital Into a One-Building Organization for COVID-19 Patients: A Resilient and Effective Response to the Pandemic - Bessis, Simon; Dinh, Aurélien; Gautier, Sylvain; Davido, Benjamin; Levy, Jonathan; Lawrence, Christine; Lot, Anne-Sophie; Bensmail, Djamel; Rech, Célia; Farcy-Afif, Muriel; Bouchand, Frédérique; de Truchis, Pierre; et al. (Frontiers in Public Health, 2022)
The COVID-19 pandemic is a unique crisis challenging healthcare institutions as it rapidly overwhelmed hospitals due to a large influx of patients. This major event forced all the components of the healthcare systems to adapt and invent new workflows. Thus, our tertiary care hospital was reorganized entirely. During the cruising phase, additional staff was allocated to a one-building organization comprising an intensive care unit (ICU), an acute care unit, a physical medicine and rehabilitation unit, and a COVID-19 screening area. The transfer of patients from a ward to another was more efficient due to these organizations and pavilion structure. The observed mortality was low in the acute care ward, except in the palliative unit. No nosocomial infection with SARS-CoV-2 was reported in any other building of the hospital since this organization was set up. This type of one-building organization, integrating all the components for comprehensive patient care, seems to be the most appropriate response to pandemics.